Socio-Economic Effects Of Large-Scale Gold Mining On Local Communities In Ghana: A Case Of Upper Denkyira West District. - Ackah, M. (University Of Ghana, 2021)
The utilisation of renewable and non-renewable natural resources is an integral part of most economies for economic growth. Gold as a non-renewable resource is obtained through excavation. The entire process of obtaining gold has been identified to have both positive and negative socio-economic effects on local communities. In Ghana, the era of industrialization and globalization has encouraged mining companies both local and multi-national in the mining sector since the 1990s which has led to expansion in the economy Ghanaian. In 2014, Perseus Mining Ghana Limited which is a large-scale mining company and the focus of this study, acquired large acres of farmlands to execute their activities. The company after the acquisition compensated the community as a whole and the individuals who were affected as well. The study was guided by 3 objectives: the first was, to analyse the differences in economic outcomes of large-scale mining on a host, resettled and nearby non-mining communities; the second was to, investigate the differences in social effects of large-scale mining on a host, resettled and non-mining communities; and the third, to examine the institutional support systems available to the community and individuals and to find out how the locals adapt to the negative effects of mining on their livelihoods. The study employed the mixed method approach by conducting a cross sectional household survey of three communities and conducting focus group discussions and key informant interviews. 350 household heads were selected using systematic random sampling for the survey and six focus group discussions were organized for two groups from each community. In addition to the focus group discussions, six key informant interviews were conducted. Analysis of the quantitative data was done by using descriptive and explanatory analysis. Thematic analysis was used for the qualitative data. The findings of the study show that the activities of large-scale mining have caused both positive and negative socio-economic effects on the livelihoods of the three communities studied. The positive effects were the generation of employment, infrastructural development and scholarships schemes to students to further their education. However, negative effects such as loss of livelihoods, food insecurity, displacement, increased social tension, increased social vices, high cost of living and health effects such as cough, cold and skin rashes were reported. The study also found out that institutional support systems present in the communities which helps the communities to maximise benefits from the mines were, traditional authorities, community support group, a support group of the mining company and government agencies. To cope with the adverse effects of the mines, respondents adopted several coping strategies such as acquiring alternative farmlands from nearby communities, ventured into other livelihoods such as trading, bought foodstuffs from nearby communities which were cheaper, used ointments to treat skin rashes and demonstrations to show their displeasure. The study recommends the provision of alternative livelihoods for affected households, the establishment of an efficient grievance redress centre by the mines, and periodic stakeholders’ engagement collaboration among government agencies.
PhD. Development Studies
Keywords: Upper Denkyira West District; Ghana; Gold Mining; Local Communities